Adaptation and validation of a questionnaire assessing patient satisfaction with pharmacy services in general hospitals - Al-Jumah, Khalaf Ali; Hassali, Mohamed Azmi; Al-Zaagi, Ibrahem (Dove Medical Press, 2014)
Objective: The aim of this study was to cross-culturally adapt the Armando Patient Satisfaction Questionnaire into Arabic and validate its use in the general population. Methods: The translation was conducted based on the principles of the most widely used model in questionnaire translation, namely Brisling’s back-translation model. A written authorization allowing translation into Arabic was obtained from the original author. The Arabic version of the questionnaire was distributed to 480 participants to evaluate construct validity. Statistical Package for Social Sciences version 17.0 for Windows was used for the statistical analysis. Results: The response rate of this study was 96%; most of the respondents (52.5%) were female. Internal consistency was assessed using Cronbach’s α, which showed that this questionnaire provides a high reliability coefficient (reaching 0.9299) and a high degree of consistency and thus can be relied upon in future patient satisfaction research.